Agriculture in the rural-urban continuum: a CGIAR research perspective - Drechsel, Pay; Keraita, Bernard N. (2015)
Thirsty and hungry cities are posing significant challenges for the urban-rural interface ranging from food security to inter-sectoral water allocation. Not only is the supply of resources to urban centres a growing challenge in low-income countries, but even more is the urban return flow, as investments in waste management and sanitation, ie the ‘ultimate food waste’, are not able to keep pace with population growth. And where polluted water is used in irrigation to feed the cities, food safety is becoming a crucial component of food security. Most affected by resource competition and pollution are the urban and peri-urban farming systems which are often driven by the informal sector. Urban waste is not only a challenge but also offers opportunities. It is in this interface between agriculture and sanitation where the CGIAR operates through its research programme on Water, Land and Ecosystems (WLE), addressing both the challenges and opportunities of urbanisation: by exploring novel perspectives and solutions to respond to changing population dynamics, resource demands, centralised water and nutrient flows, and ecosystem services under pressure.